Calibration and experiment of discrete element model parameters of Zanthoxylum bungeanum - Wang, Jian; Chen, Lin; Tang, Yingwen; Chen, Zhifan; Wu, Qingsong; Han, Dandan (Frontiers in Mechanical Engineering, 2023)
Zanthoxylum bungeanum is a characteristic spice in culinary culture. This article focuses on the lack of intrinsic and contact parameters for Zanthoxylum bungeanum and studies the intrinsic parameters of the discrete element for tribute pepper from Hanyuan. This is to provide support for the mechanized harvesting of Zanthoxylum bungeanum. The EDEM software was used to establish a discrete element model for Zanthoxylum bungeanum granules. The intrinsic parameters of Zanthoxylum bungeanum granules, such as Three-dimensional dimension, density, Poisson’s ratio, and elastic modulus, were measured through experiments. The elastic recovery coefficient, static friction coefficient, and rolling friction coefficient between Zanthoxylum bungeanum granules and Dragon Skin 30 silicone sheets were also measured. Subsequently, the elastic recovery coefficient, static friction coefficient, and rolling friction coefficient between Zanthoxylum bungeanum granules and materials, as well as between Zanthoxylum bungeanum granules were obtained through discrete element simulation experiments, steepest climb test, and Quadratic regression orthogonal rotation combination test. Finally, the Angle of repose was used for verification experiments. The results showed that the elastic recovery coefficient, static friction coefficient, and rolling friction coefficient between Zanthoxylum bungeanum granules and materials were 0.437, 0.758, and 0.0136, respectively, while those between Zanthoxylum bungeanum granules were 0.378, 0.56, and 0.0143, respectively. The error between the simulation angle of repose and the measured angle of repose was 0.204%, verifying the reliability of the discrete element model for Zanthoxylum bungeanum granules. This method is of great significance for the design and optimization of Zanthoxylum bungeanum harvesters.